Murabahah Financing, Interest Rates, Inflation, and Margin Income of Islamic Banks: Pembiayaan Murabahah, Suku Bunga, Inflasi, dan Pendapatan Margin Bank Syariah - Wijaya, Rio; Anggraini, Tuti; Indra, Ahmad Perdana (Academia Open, 2025)
Background (General): Islamic banks play a crucial role in Indonesia’s financial system, with murabahah financing serving as a primary income source. Background (Specific): While murabahah margins are fixed and independent of interest rate fluctuations, macroeconomic variables such as interest rates and inflation may still indirectly affect bank profitability. Knowledge Gap: Previous studies largely focused on annual pre-pandemic data, overlooking quarterly dynamics during the post-pandemic period, when monetary and market conditions changed significantly. Aim: This study examines the effects of murabahah financing, interest rates, and inflation on murabahah margin income in Indonesian Islamic banks during 2020–2024 using quarterly data. Results: Multiple regression analysis of 30 observations from six banks shows murabahah financing has a significant positive effect on margin income, whereas interest rates and inflation show no significant individual impact. Jointly, all three variables significantly influence margin income. Novelty: The research introduces a post-pandemic, quarterly dataset and simultaneously tests three key financial and macroeconomic variables in the murabahah context. Implications: Findings affirm the strategic importance of murabahah financing as a stable revenue driver, suggesting Islamic banks should prioritize financing expansion and operational efficiency over short-term macroeconomic fluctuations when formulating pricing and portfolio strategies. Highlight : Murabahah financing has a significant positive effect on margin income. Interest rates and inflation have no partial effect. All three variables have a simultaneous significant effect. Keywords : Murabahah Financing; Interest Rates; Inflation; Murabahah Margin Income; Islamic Banks